2012
DOI: 10.1074/jbc.m111.319277
|View full text |Cite
|
Sign up to set email alerts
|

p53 Binding Prevents Phosphatase-mediated Inactivation of Diphosphorylated c-Jun N-terminal Kinase

Abstract: Background:The p53 and c-Jun N-terminal kinase (JNK) pathways both act to initiate an apoptotic response to genotoxic stress. Results:The DNA binding domain of p53 binds to diphosphorylated JNK and prevents its dephosphorylation. Conclusion: p53 potentiates the level of JNK activity. Significance: Changes in p53 levels may coordinate the timing of an apoptotic response through regulation of JNK activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…It has been reported that the stress-dependent increase in p53 levels contributes to prolong JNK signaling by preventing its rapid dephosphorylation and inactivation by MAPK phosphatases [39]. Thus, the stabilization of p53 induced by both NBDHEX and MC3181 would contribute to maintain the JNK-dependent apoptotic response.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the stress-dependent increase in p53 levels contributes to prolong JNK signaling by preventing its rapid dephosphorylation and inactivation by MAPK phosphatases [39]. Thus, the stabilization of p53 induced by both NBDHEX and MC3181 would contribute to maintain the JNK-dependent apoptotic response.…”
Section: Discussionmentioning
confidence: 97%
“…101 In p53-deficient Drosophila wing imaginal discs irradiated with high doses of γ-rays, JNK activation and apoptosis rates were lower than in the controls. Consistent results were found in p53 knockout MEFs in which the mechanism revealed a binding domain for JNK to p53, where the interaction of JNK and p53 avoids JNK dephosphorylation by MKP-5.…”
Section: Monographsmentioning
confidence: 99%
“…Consistent results were found in p53 knockout MEFs in which the mechanism revealed a binding domain for JNK to p53, where the interaction of JNK and p53 avoids JNK dephosphorylation by MKP-5. 101 As JNK's capacity to phosphorylate c-Jun is preserved even when bound to p53, the authors proposed a model describing that simultaneous activation of JNK and p53 can cooperate to reinforce JNK-induced apoptosis. 101 Conversely, p53 binding to JNK was also described to hamper JNK activation, thus protecting the cells from UV-induced apoptosis in a lung carcinoma cell line.…”
Section: Monographsmentioning
confidence: 99%
See 1 more Smart Citation
“…7B) in Nopp140-depleted larvae. While JNK activation has been reported to be delayed in the p53-independent mechanism, 18,38 once activated, JNK is thought to induce Hid expression and thus apoptosis. 33 While we have yet to assess the abundance and activities of dFoxo and dFos in the Nopp140-depleted larvae, others have shown that Hid induction results from JNK activation via these two transcription factors.…”
Section: Uas-c42/uas-c42; P53δ/p53δ (Rnai) (Lane 4) (B) the Cross mentioning
confidence: 99%